The role of biotechnology for food consumers in developing countries - Bouis, Howarth E. (Kluwer Academic Publishers, 2000)
This article assesses the potentially enormous benefits that biotechnology and traditional plant breeding can have for reducing malnutrition among the poor through the development of more nutritious staple food crops